Determination of empirical parameters for root water uptake models - Santos, Marcos Alex dos (2016)
Physical root water uptake models can provide more insight into the mechanism, but their physical plant hydraulic parameters are hardly-ever available, making them less attractive in practical applications. Conversely, empirical root water uptake modes are more readily used because of their simplicity and lower data requirements, but their empirical parameters and ability in describing the dynamics of root water uptake need further investigation. Combining physical and empirical models might be an effective way to address these issues. In this thesis, it is tested the feasibility of deriving parameters for empirical root water uptake models by using predictions performed by an enhanced mechanistic root water uptake model. It is also reviewed the major root water uptake models that have been used together with larger eco-hydrological models and some alternatives are also presented. All these models are analyzed for different scenarios concerning soil type, atmospheric demand and root length density. Evaluation was performed by optimizing their empirical parameters so that the best fitting with the physical model is achieved. At last, further analyzes are performed for an empirical model pointed at the previous analyzes, and the empirical parameters for this model are provided for different scenarios regarding soil type, root length density R, rooting depth and potential transpiration Tp as well as for three levels of radial root hydraulic conductivity. It is shown that (i) the largely-used Feddes empirical root water uptake model performs well only under circumstances of low R -- that is for the scenarios of low root water uptake \"compensation\"-- and from medium to hight R, the model can not mimic properly the root uptake dynamics as predicted by the physical model; (ii) the Jarvis model provides good predictions only for low and medium R scenarios and for high R the model can not mimic the uptake patterns predicted by the physical model; Using the proposed reduction function in Jarvis model, that is the JMm model, helps to improve water uptake predictions; (iii) the proposed models are capable of predicting similar root water uptake patterns by the physical model and the statistical indices point them as the best alternatives to mimic root water uptake predictions by the physical model; (iv) the parameters of empirical models can be retrieved in a single experiment of soil drying-out by defining the objective function in terms of root water uptake; (v) the empirical parameters provided by the proposed model varies with the scenarios as well as its overall performance.